2015
DOI: 10.3233/jpn-2011-0486
|View full text |Cite
|
Sign up to set email alerts
|

Per-operative findings in patients operated for spinal dysraphism: A study of 96 cases

Abstract: This study was conducted to study the perioperative findings in patients of spinal dysraphism. This observational study was conducted in Neurosurgery Department of Post Graduate Medical Institute, Lady Reading Hospital, Peshawar from January 2008 to December 2009. All the patients of spinal dysraphism less than 2 years of age were included in this study, while patients with ruptured spinal dysraphism at the time of presentation and with concomitant established hydrocephalus were excluded. Data was collected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…maternal and environmental factors that may be responsible for these anomalies. In our study, males are mostly affected than female and the data is compatible with a national study done by Usman et al 12 According to our study spina bifida are more common in cousin marriage(61%), and nearly the same result was found in Dughal et al, a study in which 67% mothers having cousin marriage. 13 Through our study, we found lesion levels affected by the type of spina bifida.…”
Section: Complicationssupporting
confidence: 92%
“…maternal and environmental factors that may be responsible for these anomalies. In our study, males are mostly affected than female and the data is compatible with a national study done by Usman et al 12 According to our study spina bifida are more common in cousin marriage(61%), and nearly the same result was found in Dughal et al, a study in which 67% mothers having cousin marriage. 13 Through our study, we found lesion levels affected by the type of spina bifida.…”
Section: Complicationssupporting
confidence: 92%